Orville Park, Park's Annotated Code of the State of Georgia 1914, Penal Code, Article 3, Carrying concealed weapons, § 347 (§ 341) - (:unkn) unknown (General Publisher, 1882)
Prohibited carrying concealed any kind of metal knucks, pistol, dirk, sword in a cane, spear, bowie-knife or any other kind of knives manufactured and sold for the purpose of offense and defense. Violators guilty of a misdemeanor.
--
Keywords: CARRY - CONCEALED